Analysis of the Impact of Operational Efficiency (BOPO) and Profitability (ROA) on Credit Distribution at Bank Muamalat Indonesia (2018-2023) - Marlis Tanjung, Ami Nullah (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the influence of the Operational Efficiency Ratio (BOPO) and Return on Assets (ROA) on credit distribution at Bank Muamalat Indonesia (2018-2023) using a quantitative approach with secondary data from annual financial reports. The analytical methods include descriptive analysis and linear regression with classical assumption testing.The results indicate that high BOPO levels (averaging 98.42%) negatively affect credit distribution, except in 2022 when a BOPO reduction to 96.62% led to a 4.3% increase in credit. Low ROA (0.1%) also demonstrated positive effects, where an ROA increase to 0.09% in 2022 similarly contributed to 4.3% credit growth. These findings underscore the critical importance of operational efficiency and profitability in the credit distribution performance of Islamic banking institutions.Keywords : BOPO (Operating Expense to Operating Income Ratio), ROA (Return on Assets),Financing.